Campaign-style vs. collaborative governance: explaining coastal pollution policy implementation in China’s Bohai Sea and Japan’s Seto Inland Sea - Ye, Meng; Guo, Rui (Frontiers in Marine Science, 2025)
Marine pollution governance in semi-enclosed seas represents a significant global environmental challenge. Both China’s Bohai Sea and Japan’s Seto Inland Sea have achieved remarkable governance successes through sustained efforts in the face of similar ecological crises. However, their paths to these achievements diverge considerably. This study aims to investigate the differences in governance mechanisms that explain this phenomenon of “converging on the same destination via different routes.” Using the Most Similar Systems Design and reconstructing the classic Sabatier-Mazmanian policy implementation model, this study conducts an in-depth, multi-variable comparative analysis of these two cases, focusing on their political-economic contexts, policy designs, and implementation arenas. The findings reveal that the success in the Bohai Sea exemplifies a campaign-style mobilization model, relying on top-down political authority for resource integration and goal-driven execution, demonstrating robust short-term problem-solving capabilities. In contrast, the success in the Seto Inland Sea stems from an institutionalized collaborative model, operationalized through a dedicated legal framework that creates a multifaceted, scientifically driven, and adaptive networked governance system—ensuring long-term governance resilience and sustainability. This study deepens the applicability of policy implementation theory across diverse institutional contexts and offers insights for exploring hybrid governance pathways that integrate the strengths of both models, thereby advancing sustainable management of global marine ecosystems.